A modified computer-assisted colorimetric microtitre assay (MTT) to assess in vitro radiosensitivity of V79, CaSki, HeLa and WiDr cells - Eble, Michael J.; Hensley, Frank W.; Flentje, Michael; Schlotz, Annette; Wannenmacher, Michael (International journal of radiation biology, 1994)
The non-clonogenic MTT assay, based on the reduction of a tetrazolium salt to a purple formazan precipitate by living cells, was modified and a new procedure of analysis is proposed. The colorimetric assay could be performed semiautomatically using microtitre plate reader connected to a personal computer. Data are processed and plotted with a customized program. To ensure that both control and irradiated microtitre plates contain exponentially growing cells at the time of analysis, the calculation of relative survival is based on a series of well-defined cell numbers initially seeded. To make the two endpoints of non-clonogenic and clonogenic assays comparable, i.e. counting of living cells versus counting of colonies, radiation-induced progression delay was incorporated into the calculation. Radiation-induced cell killing and progression delay could be determined in a single analysis, but in an independent way. X-ray survival curves were generated for V79, CaSki, WiDr and HeLa cells using the non-clonogenic and a standard clonogenic assay. Using the linear-quadratic formula, the resulting parameters α,β and the mean inactivation dose were not significantly different. The described assay is a feasible and reproducible technique for determination of cellular survival, which may be able to incorporate progression delay. The equivalence to a clonogenic survival assay could be proven.
Gesehen am 06.02.2025
Elektronische Reproduktion der Druck-Ausgabe 3. Juli 2009